EXPERT ROUNDTABLE ON THE ELECTION OF GOVERNORS - Kovin, V.S. (Perm Federal Research Centre Journal, 2015)
In July, the PSC the Ural branch of the Russian Academy of Sciences held in Perm an expert roundtable on "The Elections of the Heads of the Regionsin the Russian Federation in 2014: Reasons, Expectations, Predictions and State of Affairs". Leading Russian researchers of the regional political processes evaluated the past 2014 elections of governors as non-competitive and as a kind of "referenda of trust" in favour ofthe current heads of the regions.